Literasi Qurani Berbasis Teknologi: Mengintegrasikan Bahasa, Karakter, dan Digitalisasi di Rumah Tahfidz” - Indra, Novalia; Mulyadi, Jendri; Rahmawati, Elmi (LPPM Universitas Dharma Andalas, 2025)
The development of digital technology has brought about significant changes in the world of education, including in religious institutions such as Tahfidz Houses, which play a role in educating the Quranic generation through reading, memorizing, understanding, and practicing the values ​​of the Quran. However, learning activities in Tahfidz Houses still focus on reading and memorization skills, while aspects of understanding meaning, strengthening character, and utilizing technology are not yet optimal. This Community Service Program (PKM) aims to develop a model of